University-industry: Linkage status and perception of barriers to scientific research and innovation as a tool for management and development in small and medium-sized companies - Alarcon Avendaño, Fredy Odon (2022)
To determine the association between the state of university-business linkage and the perception of barriers to scientific research and innovation as a management and development tool in small and medium enterprises, Tacna. Method: observational study, relational research level, the methodological strategy used was quantitative. Out of a total of 1,422 formally constituted companies that generate products that can be improved or innovated in the productive field in the Tacna region, we were able to work with 172. Results: 14.5% of the companies were mainly engaged in the manufacture of bakery products, followed by 12.8% in the manufacture of garments and 10.5% in the distillation and blending of alcoholic beverages. 98.8% were privately owned. The 85.5% had less than 10 workers. Formal linkages with universities accounted for 1.2%. Companies identified a medium (34.3%) and low (34.3%) level of barriers to innovation opportunities. Conclusions: The impact of innovations that had an impact on the product was high, and 92.2% were due to taking advantage of an idea or published novelties. The impact of innovation on processes was medium, with 51.5% being due to the reduction of materials and energy in production.